Dissecting genomic regions and candidate genes for pod borer resistance and component traits in pigeonpea minicore collection - Moghiya, Abhinav; Munghate, R.S.; Sharma, Vinay; Mishra, Suraj Prashad; Jaba, Jagdish; Gaurav, Shailendra Singh; Gangurde, Sunil S.; Dube, Namita; Rangari, Sagar Krushnaji; Roychowdhury, Rajib; Gangashetty, Prakash; Sharma, Hari Chand; et al. (Frontiers in Plant Science, 2025)
BackgroundPigeonpea is an important leguminous food crop primarily grown in tropical and subtropical regions of the world and is a rich source of high-quality protein. Biotic (weed, disease, and insect pests) and abiotic stresses have significantly reduced the production and productivity of pigeonpea. Helicoverpa armigera, also known as the pod borer, is a major pest in pigeonpea. A substantial investigation is needed to comprehend the genetic and genomic underpinnings of resistance to H. armigera. Genetic improvement by genomics-assisted breeding (GAB) is an effective approach for developing high-yielding H. armigera-resistant cultivars. Still, no genetic markers and genes linked to this key trait have been detected in pigeonpea. In this context, a set of 146 pigeonpea minicore accessions were evaluated for four H. armigera-resistant component traits, namely, pod borer resistance (PBR), days to 50% flowering (DF), days to maturity (DM), and grain yield (GY), for three consecutive seasons under field conditions.ResultsPhenotypic data of pod borer resistance and component traits, along with the whole-genome resequencing (WGRS) data for 4,99,980 single nucleotide polymorphisms (SNPs), were utilised to perform multi-locus genome-wide association study (GWAS) analysis. Two models [settlement of MLM under progressively exclusive relationship (SUPER) and fixed and random model circulating probability unification (FarmCPU)] detected 14 significant marker–trait associations (MTAs) for PBR and three component traits. The MTAs with significant effect were mainly identified on chromosomes CcLG02, CcLG04, CcLG05, CcLG07, and CcLG11. These MTAs were subsequently delineated with key candidate genes associated with pod borer resistance (probable carboxylesterase 15, microtubule-associated protein 5, FAR1-RELATED SEQUENCE, and omega-hydroxypalmitate O-feruloyl transferase 4), days to maturity (RING-H2 finger protein ATL7 and leucine-rich repeat receptor-like protein kinase), and grain yield (secretory carrier-associated membrane protein and glutaredoxin-C5 chloroplastic).ConclusionThese research findings reported significant MTAs and candidate genes associated with pod borer resistance and component traits. Further lab-based pod bioassay screening identified four minicore accessions, namely, ICP 10503, ICP 655, ICP 9691, and ICP 9655 (moderately resistant genotypes), showing the least damage rating and larval weight gain %, compared to the susceptible checks. After validating the significant MTAs, the associated SNP markers can be effectively utilised in indirect selection, which offers potential gains for such quantitative traits with low heritability and can improve insect management more sustainably. The significant MTAs, candidate genes, and resistant accessions reported in this study may be utilised for the development of pod borer-resistant pigeonpea varieties.